Film coating method for improving hardness of AR film of diaphragm
By depositing Ge film layer and Si film layer on the substrate of the window sheet AR film, the problem of insufficient hardness of the existing AR film is solved, and the hardness improvement is achieved while satisfying the transmittance, avoiding the risk of scratches during the detector production process.
Patent Information
- Application Number
- CN202411669616.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-25
AI Technical Summary
The existing window sheet AR film has insufficient hardness and is easily scratched during the detector production process, affecting the performance of the detector.
The Ge film layer and the Si film layer are deposited in sequence on the first and second surfaces of the window sheet substrate, the Si film layer is the outermost layer, and the Ge film layer is the transition layer between the ZnS film layer and the Si film layer, thereby increasing the hardness of the AR film.
It effectively avoids scratches in subsequent processes, while maintaining good transmittance, meeting the balance between hardness improvement and transmittance requirements.
Smart Images

Figure CN119685749A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to detector technology, and more particularly to a coating method for improving the hardness of an AR film of a window piece. Background Art
[0002] In the existing window AR (Anti-Reflection) film system design, ZnS is usually used as the outermost material of the film system. However, because ZnS itself is not hard enough, the detector manufacturing process goes through substrate deposition, slicing and granulation, window sealing, imaging detection and other steps. During the execution of these steps, human factors (scratches by nails and instruments, etc.) are introduced, which can easily scratch the surface of the AR film (i.e., the ZnS film layer). The scratched surface of the ZnS film layer will increase the risk of affecting or even damaging the detector performance. Summary of the invention
[0003] In view of the problems existing in the background technology, an object of the present disclosure is to provide a coating method for improving the hardness of an AR film of a window piece, which can improve the hardness of the film system of the window piece while satisfying the transmittance.
[0004] Therefore, a coating method for improving the hardness of an AR film on a window piece includes the following steps: S1, placing a window piece substrate into a fixture, hanging the fixture with the window piece substrate placed thereon into a cavity of a coating machine, the window piece substrate refers to a substrate in the process before the AR film patterning process is completed in the window piece process, and setting the temperature of the cavity; S2, cleaning the ion source; S3, depositing an AR film system on the first side of the window piece substrate, the outermost layer of the AR film system on the first side of the window piece substrate is a ZnS film layer; S4, depositing a Ge film layer and a Si film layer in sequence on the ZnS film layer of the AR film system; S5, after the AR film system, the Ge film layer and the Si film layer are deposited on the first side of the window piece substrate, the cavity is cooled down, and the fixture is taken out together with the window piece substrate on which the AR film system, the Ge film layer and the Si film layer are deposited on the first side; S6, repeating steps S1 to S5, and depositing the same AR film system, Ge film layer and Si film layer on the second side of the window piece substrate.
[0005] The beneficial effects of the present disclosure are as follows: In the coating method for improving the hardness of the AR film of the window piece according to the present disclosure, a Ge film layer and a Si film layer are sequentially deposited on the AR film system whose outermost layer is a ZnS film layer on the first surface of the window piece substrate, and the Si film layer is the outermost layer. The Ge film layer serves as a transition layer between the ZnS film layer and the Si film layer. The Si film layer itself has a high hardness and serves as a hardening layer, which can effectively prevent the window piece from being scratched (for example, scratched by nails, scratched by instruments, etc.) during the execution of the processes of dicing, window sealing, imaging detection, etc. after the completion of step S6 (i.e., coating). In addition, as verified by the test process, the plated Ge film layer and Si film layer do not have a significant effect on the transmittance of the window piece. That is, the hardness of the film system of the window piece is improved while satisfying the transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 It is a schematic diagram of the film layer structure of Comparative Example 1.
[0007] Figure 2 This is a transmittance simulation data diagram of Comparative Example 1.
[0008] Figure 3 It is a schematic diagram of the film layer structure of Example 1.
[0009] Figure 4 This is a transmittance simulation data diagram of Example 1.
[0010] Figure 5 It is a curve chart of the transmittance actually measured in Comparative Example 1 and Example 1.
[0011] Figure 6 are photographs of windows from Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0012] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0013] [Coating method to improve the hardness of window AR film]
[0014] Combination Figure 2 According to the present disclosure, the coating method for improving the hardness of the window AR film includes the following steps:
[0015] S1, put the window substrate into the fixture, and hang the fixture with the window substrate into the cavity of the coating machine. The window substrate refers to the substrate before the AR film patterning process is completed in the window process, and the temperature of the cavity is set;
[0016] S2, ion source cleaning;
[0017] S3, depositing an AR film system on the first surface of the window substrate, wherein the outermost layer of the AR film system on the first surface of the window substrate is a ZnS film layer;
[0018] S4, depositing a Ge film layer and a Si film layer in sequence on the ZnS film layer of the AR film system;
[0019] S5, after the AR film system, the Ge film layer and the Si film layer are deposited on the first side of the window substrate, the chamber is cooled down, and the fixture together with the window substrate on which the AR film system, the Ge film layer and the Si film layer are deposited on the first side are taken out;
[0020] S6, repeating steps S1 to S5, depositing the same AR film system, Ge film layer and Si film layer on the second surface of the window substrate.
[0021] In the coating method for improving the hardness of the AR film of the window piece according to the present disclosure, a Ge film layer and a Si film layer are sequentially deposited on the AR film system whose outermost layer is a ZnS film layer on the first surface of the window piece substrate, and the Si film layer is the outermost layer. The Ge film layer serves as a transition layer between the ZnS film layer and the Si film layer. The Si film layer itself has a high hardness and serves as a hardening layer, which can effectively prevent the window piece from being scratched (for example, scratched by nails, scratched by instruments, etc.) during the execution of the processes of dicing, granulation, window sealing, imaging detection, etc. after the completion of step S6 (i.e., coating). In addition, as verified in the subsequent test process, the plated Ge film layer and Si film layer do not have a significant effect on the transmittance of the window piece. That is, the hardness of the film system of the window piece is improved while satisfying the transmittance.
[0022] In one example, in step S1, the window substrate is a Si substrate, and the thickness of the Si substrate is 725 μm. For example, in step S1, the temperature of the chamber is set to 70°C.
[0023] In one example, step S2 is: the vacuum coating machine starts to evacuate, and the vacuum degree reaches 4×10 -3 Pa, turn on the Kaufman ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The parameters of the Kaufman ion source are: anode voltage is 80V, anode current is 50mA, neutralization current is 12A, neutralization gas flow rate is 20sccm, and argon gas flow rate accounts for 100%.
[0024] For example, the ZnS film layer in step S3 is deposited by resistance evaporation and assisted by a Kaufman ion source, and the deposition rate of the ZnS film layer is The deposition thickness of the ZnS film layer is 1300nm; the process parameters of the Kaufman ion source assisted deposition of the ZnS film layer are: anode voltage of 70V, anode current of 80mA, neutralization current of 14A, neutralization gas flow rate of 20sccm, and argon gas flow rate of 100%.
[0025] In one example, step S4 is: at a vacuum degree of 4×10 -3 Pa and the chamber temperature of the coating machine was controlled at 70°C. Ge film layer and Si film layer were deposited on the ZnS film layer of the AR film system in sequence. The Ge film layer was deposited by electron beam evaporation and assisted by Kaufman ion source. The deposition rate of the Ge film layer was The deposition thickness of the Ge film layer is 10 nm, and the Si film layer is deposited by electron beam evaporation and assisted by Kaufman ion source. The deposition rate of the Si film layer is The thickness of the Si film layer is 10nm; the process parameters of the Kaufman ion source assisted deposition of the Ge film layer and the Si film layer are: anode voltage of 70V, anode current of 80mA, neutralization current of 14A, neutralization gas flow rate of 20sccm, and argon gas flow rate of 100%.
[0026] In one example, in step S3 and step S4, argon gas is introduced and evacuated when depositing each film layer to maintain a flowing constant vacuum; the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller, and the crystal controller controls the corresponding operation of a new crystal oscillator piece among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.85MHz.
[0027] In one example, in step S5, after the deposition is completed, the chamber is kept at a constant temperature of 70°C for 10 minutes. For example, in step S5, the door is opened to take out the parts after the temperature drops below 50°C.
[0028] [test]
[0029] Comparative Example 1
[0030] Part 1: AR film system simulation
[0031] Reference Figure 1 The film system is window substrate / Ge / ZnS / AIR, where the window substrate is Si substrate, AIR is air, and the same film system is used on both sides of the window substrate. The film thickness of the film layer is optimized in TFCalc software. After optimization, the film thickness of the Ge film layer is 100nm, and the film thickness of the ZnS film layer is 1300nm. The average transmittance of the optimized window substrate and the film systems on both sides in the 8-14μm band is 83.17%, as shown in Figure 2 shown.
[0032] Part 2: Film Coating
[0033] The coating method of Comparative Example 1 adopts the following steps:
[0034] Sa, the window substrate is placed in a fixture, and the fixture with the window substrate is hung in the cavity of the coating machine. The coating machine is a Siwork ZZS1350-III. The window substrate refers to the substrate in the process before the AR film patterning process is completed in the window process. The window substrate is a Si substrate with a thickness of 725μm. The temperature of the cavity is set to 70°C;
[0035] Sb, ion source cleaning, vacuum coating machine start vacuuming, vacuum degree reaches 4×10 -3 Pa, open the Kaufman ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the Kaufman ion source are: anode voltage is 80V, anode current is 50mA, neutralization current is 12A, neutralization gas flow rate is 20sccm, and argon gas flow rate accounts for 100%;
[0036] Sc, AR film system deposited on the first side of the window substrate,
[0037] At vacuum degree 4×10 -3 Pa and the chamber temperature of the coating machine is controlled at 70°C, and a Ge film layer and a ZnS film layer of the AR film system are sequentially deposited on the window substrate;
[0038] The Ge film layer was deposited by electron beam evaporation and assisted by a Kaufman ion source. The deposition rate of the Ge film layer was The deposition thickness of the Ge film is 10nm.
[0039] The ZnS film layer was deposited by resistance evaporation and assisted by a Kaufman ion source. The deposition rate of the ZnS film layer was The deposition thickness of the ZnS film is 1300nm
[0040] The process parameters of Kaufman ion source assisted deposition of Ge and ZnS films are:
[0041] The anode voltage is 70V, the anode current is 80mA, the neutralization current is 14A, the neutralization gas flow rate is 20sccm, and the argon gas flow rate accounts for 100%;
[0042] When depositing each film layer, argon gas is introduced and vacuum is drawn to maintain a constant flow vacuum;
[0043] The film thickness is monitored by using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller using a crystal oscillator method, the crystal controller controls a new crystal oscillator of the plurality of crystal oscillators to work correspondingly, and the crystal oscillator frequency is not less than 5.85 MHz;
[0044] Sd, after the AR film system is deposited on the first side of the window substrate, the chamber is kept at a constant temperature of 70°C for 10 minutes, and when the temperature drops to 50°C, the fixture and the window substrate with the AR film system deposited on the first side are taken out;
[0045] Se, repeat steps Sa to Sd to deposit the same AR film system on the second surface of the window substrate.
[0046] Example 1
[0047] Part 1: Simulation of the film system consisting of AR film and additional Ge and Si layers
[0048] Reference Figure 3 , the film system is window substrate / Ge / ZnS / Ge / Si / AIR, where the window substrate is Si substrate, AIR is air, the same film system is used on both sides of the window substrate, and the film thickness of the film layer is optimized in TFCalc software. After optimization, the film thickness of the Ge film layer in the AR film is 100nm, the film thickness of the ZnS film layer in the AR film is 1300nm, the film thickness of the added Ge film layer is 10nm, and the film thickness of the Si film layer is 10nm. The average transmittance of the optimized window substrate together with the film systems on both sides in the 8-14μm band is 82.86%, as shown Figure 4 shown.
[0049] Part 2: Film Coating
[0050] The coating method of Example 1 adopts the following steps:
[0051] S1, the window substrate is placed in a fixture, and the fixture with the window substrate is hung in the cavity of the coating machine. The coating machine is the Siwork ZZS1350-III. The window substrate refers to the substrate before the AR film patterning process is completed in the window process. The substrate is a Si substrate with a thickness of 725μm. The temperature of the cavity is set to 70°C.
[0052] S2, ion source cleaning, vacuum coating machine starts to evacuate, vacuum degree reaches 4×10 -3 Pa, open the Kaufman ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the Kaufman ion source are: anode voltage is 80V, anode current is 50mA, neutralization current is 12A, neutralization gas flow rate is 20sccm, and argon gas flow rate accounts for 100%;
[0053] S3, AR film system is deposited on the first side of the window substrate.
[0054] At vacuum degree 4×10 -3Pa and the chamber temperature of the coating machine is controlled at 70°C, and a Ge film layer and a ZnS film layer of the AR film system are sequentially deposited on the window substrate;
[0055] The Ge film layer was deposited by electron beam evaporation and assisted by a Kaufman ion source. The deposition rate of the Ge film layer was The deposition thickness of the Ge film is 10nm.
[0056] The ZnS film layer was deposited by resistance evaporation and assisted by a Kaufman ion source. The deposition rate of the ZnS film layer was The deposition thickness of the ZnS film is 1300nm.
[0057] The process parameters of Kaufman ion source assisted deposition of Ge and ZnS films are:
[0058] The anode voltage is 70V, the anode current is 80mA, the neutralization current is 14A, the neutralization gas flow rate is 20sccm, and the argon gas flow rate accounts for 100%;
[0059] When depositing each film layer, argon gas is introduced and vacuum is drawn to maintain a constant flow vacuum;
[0060] The film thickness is monitored by using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller using a crystal oscillator method, the crystal controller controls a new crystal oscillator of the plurality of crystal oscillators to work correspondingly, and the crystal oscillator frequency is not less than 5.85 MHz;
[0061] S4, depositing a Ge film layer and a Si film layer in sequence on the ZnS film layer of the AR film system,
[0062] At vacuum degree 4×10 -3 Pa and the chamber temperature of the coating machine is controlled at 70°C, and a Ge film layer and a Si film layer are sequentially deposited on the ZnS film layer of the AR film system.
[0063] The Ge film layer was deposited by electron beam evaporation and assisted by a Kaufman ion source. The deposition rate of the Ge film layer was The deposition thickness of the Ge film is 10nm.
[0064] The Si film layer was deposited by electron beam evaporation and assisted by a Kaufman ion source. The deposition rate of the Si film layer was The thickness of the Si film layer is 10nm;
[0065] The process parameters of Kaufman ion source assisted deposition of Ge and Si films are: anode voltage 70V, anode current 80mA, neutralization current 14A, neutralization gas flow rate 20sccm, argon gas flow rate 100%;
[0066] When depositing each film layer, argon gas is introduced and vacuum is drawn to maintain a constant flow vacuum;
[0067] The film thickness is monitored by using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller using a crystal oscillator method, the crystal controller controls a new crystal oscillator of the plurality of crystal oscillators to work correspondingly, and the crystal oscillator frequency is not less than 5.85 MHz;
[0068] S5, after the AR film system, Ge film layer and Si film layer are deposited on the first side of the window substrate, the chamber is kept at a constant temperature of 70° C. for 10 minutes, and when the temperature drops to 50° C., the fixture is taken out together with the window substrate on which the AR film system, Ge film layer and Si film layer are deposited on the first side;
[0069] S6, repeating steps S1 to S5, depositing the same AR film system, Ge film layer and Si film layer on the second surface of the window substrate.
[0070] In Comparative Example 1, Figure 2 It can be seen that the average transmittance of the optimized window substrate and the films on both sides in the 8-14 μm band is 83.17%; in Example 1, Figure 4 It can be seen that the average transmittance of the optimized window substrate together with the films on both sides in the 8-14μm band is 82.86%. After adding Ge and Si film layers to the AR film, the transmittance decreases by 0.31%.
[0071] Figure 5 The curve diagram of the transmittance actually measured after coating the second part of the film system of Comparative Example 1 and Example 1 is given. Figure 5 It can be seen that the transmittance of the window substrate and the films on both sides in the 8-14μm band is not much different, and Figure 5 The transmittance curve of Figure 2 and Figure 4 The transmittance curves are not much different. This shows that, whether in the simulation part or in the film coating part, adding Ge film and Si film layers on the basis of AR film can meet the transmittance requirements. Because the Si film layer is the outermost layer, the Si film layer itself has a high hardness. As a hardening layer, it can effectively prevent the window sheet from being scratched (such as scratched by nails, scratched by instruments, etc.) during the execution of the processes of dicing, window sealing, imaging detection, etc. after the completion of step S6.
[0072] After the film coating of Comparative Example 1 and Example 1 was completed, the substrate and the film systems on both sides were diced into particles, and the number of diced particles was 60 (i.e., 60 window pieces), and then the 60 window pieces were subjected to window sealing (i.e., forming detectors) and imaging detection processes. After the imaging detection process was completed, the number of surface scratches of the window pieces of the formed detectors was visually inspected and counted.
[0073] The number of surface scratches on the window plate from Comparative Example 1 was 50; the number of surface scratches on the window plate from Example 1 was zero. Figure 6 The photos of the window sheets from Comparative Example 1 and Example 1 are given. Figure 6 The left picture is a picture of the window plate (with scratches) from Comparative Example 1. Figure 6 The right picture is a photograph of the window plate from Example 1.
[0074] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A coating method for improving the hardness of an AR film on a window, characterized in that: Includes steps: S1, put the window substrate into the fixture, and hang the fixture with the window substrate into the cavity of the coating machine. The window substrate refers to the substrate before the AR film patterning process is completed in the window process, and the temperature of the cavity is set; S2, ion source cleaning; S3, depositing an AR film system on the first surface of the window substrate, wherein the outermost layer of the AR film system on the first surface of the window substrate is a ZnS film layer; S4, depositing a Ge film layer and a Si film layer in sequence on the ZnS film layer of the AR film system; S5, after the AR film system, the Ge film layer and the Si film layer are deposited on the first side of the window substrate, the chamber is cooled down, and the fixture together with the window substrate on which the AR film system, the Ge film layer and the Si film layer are deposited on the first side are taken out; S6, repeating steps S1 to S5, depositing the same AR film system, Ge film layer and Si film layer on the second surface of the window substrate.
2. The coating method for improving the hardness of the AR film of the window according to claim 1, characterized in that: In step S1 , the window substrate is a Si substrate, and the thickness of the Si substrate is 725 μm.
3. The coating method for improving the hardness of the AR film of the window according to claim 1, characterized in that: In step S1, the coating machine is a Siwork ZZS1350-III.
4. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: In step S1 , the temperature of the chamber is set to 70° C.
5. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: Step S2 is: the vacuum coating machine starts to evacuate the vacuum to a degree of 4×10 -3 Pa, turn on the Kaufman ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The parameters of the Kaufman ion source are: anode voltage is 80V, anode current is 50mA, neutralization current is 12A, neutralization gas flow rate is 20sccm, and argon gas flow rate accounts for 100%.
6. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: The ZnS film layer in step S3 is deposited by resistance evaporation method and assisted by Kaufman ion source. The deposition rate of the ZnS film layer is The deposition thickness of the ZnS film layer is 1300nm. The process parameters of the Kaufman ion source assisted deposition of the ZnS film layer are: anode voltage of 70V, anode current of 80mA, neutralization current of 14A, neutralization gas flow rate of 20sccm, and argon gas flow rate of 100%.
7. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: Step S4 is: At vacuum degree 4×10 -3 Pa and the chamber temperature of the coating machine is controlled at 70°C, and a Ge film layer and a Si film layer are sequentially deposited on the ZnS film layer of the AR film system. The Ge film layer was deposited by electron beam evaporation and assisted by a Kaufman ion source. The deposition rate of the Ge film layer was The deposition thickness of the Ge film is 10nm. The Si film layer was deposited by electron beam evaporation and assisted by a Kaufman ion source. The deposition rate of the Si film layer was The thickness of the Si film layer is 10nm; The process parameters of the Kaufman ion source assisted deposition of the Ge film layer and the Si film layer are: anode voltage of 70V, anode current of 80mA, neutralization current of 14A, neutralization gas flow rate of 20sccm, and argon gas flow rate of 100%.
8. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: In step S3 and step S4, When depositing each film layer, argon gas is introduced and vacuum is drawn to maintain a constant flow vacuum; The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. The crystal controller controls the corresponding operation of a new crystal oscillator piece among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.85 MHz.
9. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: In step S5, after the deposition is completed, the chamber is kept at a constant temperature of 70°C for 10 minutes.
10. The coating method for improving the hardness of the AR film of a window according to claim 1, characterized in that: In step S5, the door is opened to take out the items when the temperature drops below 50°C.
Citation Information
Cited By
Preparation method of diaphragm
CN122254432A